(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Phosphorus ion implantation into silicon substrates is a critical process in semiconductor fabrication, influencing dopant distribution and damage generation. This study employs SRIM/TRIM simulations to analyse the effect of phosphorus ion energies ranging from 10 kev to 50 kev on implantation characteristics in silicon. Key metrics, including backscattered ions, vacancy production, and spatial distribution of implanted ions, were examined. Results reveal a monotonic increase in vacancy formation and ion range with increasing energy, while backscattering decreases initially and then slightly rises at 50 keV. The data indicate enhanced penetration depth and lateral spread with energy, vital for optimising ion implantation protocols in silicon-based microelectronics. The findings offer a predictive insight into damage evolution and dopant behaviour for energy-controlled doping processes.